Application of Artificial Intelligence in Teaching Bulgarian Literature - Hristo Kamenov (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
The aim of the study was to identify the possibilities of effective use of intelligent digital technologies in teaching the Bulgarian literature and analysing literary texts within the framework of philological education. The research involved a comprehensive study of the state of digitalisation of literary education in Bulgaria, as well as experimental testing of a number of digital tools in the learning environment of Sofia University. As a result, it was found that the most common digital solutions at the school level were adaptive educational platforms with the possibility of individualising the learning process and providing real-time feedback, while in higher education the spread of such technologies remained fragmented and mainly concentrated in technical specialities. The experimental implementation of language processing tools in teaching literature has shown a positive impact on the depth of students’ interpretive skills. There was an increase in the accuracy of the analysis of literary content, the ability to identify latent themes and semantic connections, and an increase in motivation to learn. According to the survey, 94% of students confirmed an improved understanding of the author’s ideas, 86% identified new themes and interpretive lines, 72% showed an increased interest in literature, and an expert assessment showed a 27% increase in the accuracy of students’ written interpretations. The study also revealed significant limitations, including technical inequality between regions of the country, insufficient support for the Bulgarian language from mainstream linguistic models, risks of losing transparency in assessment, and the lack of clear ethical regulations for the use of technology in education.